Recensioni - Gemma Carotenuto (1); Bruno D'Amore (2); Michele Canducci (3, 4); Agnese Del Zozzo (5); Giovanni Giuseppe Nicosia (6) (Didattica della Matematica, 2020)
1. “L’infinito sai cos’è?” http://www.matematicando.supsi.ch/index.php/2020/02/20/linfinito-sai-cose/